Occurrence of citrus viroids in Costa Rica - Villalobos, W (Universidad de Costa Rica, 1997)
A survey for citrus viroids was conducted in ¡he major citrus comrnercial growing areas in Costa Rica. Screening of 36 sweet orange and 12 ¡cmon trees resulted in the detection of members of four of Ihe five cilrus viroid groups as detennined by nucleic acid hybridization using specific RNA probes and polyrnerase chain reaction (PCR) using specific oligol1ucleotide primers. CEVd, CVd-Ila, CVD-lIb and CVd-IH viroids were found to be widespread in the three main regions of comrnercial citurs production. CVd-Ib was only found in lernon in Nicoya.